Daughter of the deep - Riordan, Rick (Disney Hyperion, 2021)
In this story inspired by Jules Verne's "20,000 Leagues Under the Sea," Ana Dakkar, a freshman at Harding-Pencroft Academy, a five-year high school that graduates the best marine scientists, naval warriors, navigators, and underwater explorers in the world, makes astounding discoveries about her heritage and puts her leadership skills to the test against deadly enemies from a rival school.